Analyzing tax reforms using the Swedish Labour Income Microsimulation Model - Jacob Lundberg (Uppsala University, Department of Economics, 2017)
Labour income taxation is a central policy topic because labour income makes up the majority of national income and most taxes are in the end taxes on labour. In order to quantify how behavioural responses of labour income earners affect tax revenue, the Swedish Labour Income Microsimulation Model (SLIMM) is constructed and used to evaluate tax reforms. The model simulates taxable income responses, participation responses and income effects. Elasticities are calibrated to match midpoints of estimates found in the quasiexperimental literature. SLIMM is solidly microfounded and uses administrative register data. The model is used to analyze changes to the earned income tax credit (EITC), municipal income taxes and the central government income tax paid by high-income earners. The simulations indicate that the EITC has increased employment by 128,000 and has a degree of self-financing of 21 percent. Almost half of the revenue increase from higher municipal tax rates would disappear due to behavioural responses. Tax cuts for the richest fifth of working Swedes are completely self-financing.
urn:nbn:se:uu:diva-333805
Keywords: 330